Intraoperative Cerebrospinal Fluid Leak in Extradural Spinal Tumor Surgery - Alexander E. Ropper; Kevin T. Huang; Allen L. Ho; Judith M. Wong; Stephen V. Nalbach; John H. Chi (Neurospine, 2018)
Objective Patients with extradural spine tumors are at an increased risk for intraoperative cerebrospinal fluid (CSF) leaks and postoperative wound dehiscence due to radiotherapy and other comorbidities related to systemic cancer treatment. In this case series, we discuss our experience with the management of intraoperative durotomies and wound closure strategies for this complex surgical patient population. Methods We reviewed our recent single-center experience with spine surgery for primarily extradural tumors, with attention to intraoperative durotomy occurrence and postoperative wound-related complications. Results A total of 105 patients underwent tumor resection and spinal reconstruction with instrumented fusion for a multitude of pathologies. Twelve of the 105 patients (11.4%) reviewed had intraoperative durotomies. Of these, 3 underwent reoperation for a delayed complication, including 1 epidural hematoma, 1 retained drain, and 1 wound infection. Of the 93 uncomplicated index operations, there were a total of 9 reoperations: 2 for epidural hematoma, 3 for wound infection, 2 for wound dehiscence, and 2 for recurrent primary disease. One patient was readmitted for a delayed spinal fluid leak. The average length of stay for patients with and without intraoperative durotomy was 7.3 and 5.9 days, respectively, with a nonsignificant trend for an increased length of stay in the durotomy cases (p=0.098). Conclusion Surgery for extradural tumor resections can be complicated by CSF leaks due to the proximity of the tumor to the dura. When encountered, a variety of strategies may be employed to minimize subsequent morbidity.